Tendencies of development of the theory of controlling in system managements - S. M. Bychkova; E. A. Zhidkova (Путеводитель предпринимателя, 2020)
In article development of the theory of controlling according to steps of industrial revolution is considered. From a position ofsystem approach process of existence of a control system is presented.